DISEASES, THAT ARE MOST COMMONLY DISGUISED TEMPOROMANDIBULAR DISORDERS - Telishevskaya, Y.D. (World of Medicine and Biology, 2013)
The need for a multidisciplinary approach to dental patients is substantiated in the article, since there is a significant number of pathologies that can masquerade as temporomandibular disorders.